Immobilization of Enzyme–Polymer Hybrids and Nanozymes Through Electrostatic Interactions: Toward Multicatalytic Microreactors with Controlled Nanoarchitecture - Aitor Ontoria; Irene Alonso‐Sampedro; Yixuan Yan; Ayşe Latif; Ben F. Spencer; Aitor Larrañaga; Ana Beloqui; Christos Tapeinos (Small Science)
The optimal allocation of catalysts and their precise compartmentalization are vital to ensure efficient cascade reactions. The layer‐by‐layer approach offers the possibility of assembling various building blocks onto templates of different sizes and shapes, thus representing a powerful tool for fabricating multicatalytic reactors with controlled nanoarchitecture. However, this process usually relies on electrostatic interactions between building blocks, which means a limitation when working with natural enzymes. Accordingly, both the loading capacity and control over membrane architecture are compromised by the inherent surface charge of the enzymes. Here, this study introduces a modular strategy to assemble engineered enzyme‐polymer hybrids and inorganic nanozymes onto colloidal templates, giving rise to multicatalytic reactors. The surface charge of the engineered enzyme–polymer hybrids can be finely tuned, allowing their à‐la‐carte assembly into multilayer membranes. Following this approach, the distance between catalytic units and their arrangement on colloidal templates at the nano‐ and micrometer scale can be precisely controlled, resulting in optimized configurations with enhanced cascade efficiency. The synthesized multicatalytic reactors can reduce the metabolic activity of human pancreatic stellate cells, confirming their functional activity in biological microenvironments and highlighting their potential for biomedical applications.